Penguatan Nilai-Nilai Keagamaan Berbasis Pendidikan Karakter pada Siswa SMP Muhammadiyah 2 Karanganyar dan SMP Negeri 2 Tasikmadu Karanganyar - Tarno, Tarno; Subandono, Joko (TSAQOFAH, 2026)
Character education grounded in religious values plays a strategic role in shaping students’ personalities to be faithful, pious, and of noble character; however, the challenges of globalization and the development of information technology have weakened the internalization of religious values among adolescents, particularly at the lower secondary level. This study aimed to analyze forms of strengthening religious values based on character education, the roles of teachers and school culture, as well as the supporting and inhibiting factors in its implementation at SMP Muhammadiyah 2 Karanganyar and SMP Negeri 2 Tasikmadu Karanganyar. A qualitative approach with a multiple case study design was employed, with data collected through in-depth interviews, participatory observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings show that the reinforcement of religious values is carried out through the integration of religious values into learning, the habituation of worship, teacher role modeling, and the development of a religious school culture, with teachers and school culture serving as key determinants of success. The study also indicates that the influence of the social environment, digital media, and time constraints constitute the main obstacles in implementing character education based on religious values. The study concludes that strengthening synergy among schools, teachers, and parents is essential to optimize the reinforcement of religious values within students’ character education at the junior secondary school level.